Patterns of Dietary Nutrient Consumption among Pregnant M others in Dhaka City, Bangladesh - Karim, Kazi Muhammad Rezaul; Tasnim, Tasmia (Bangladesh Journal of Nutrition, 2014)
Pregnancy is a condition of higher nutrient requirement but in developing country like Bangladesh most of the pregnant women can not meet their nutrient requirement and some time they are neglected in the family. The purpose of the study was to assess the nutritional status and dietary nutrient intake by the pregnant women, in Dhaka city, Bangladesh. Under a cross-sectional design, 30 healthy non-pregnant as well as 130 pregnant women, at 3 different trimesters of pregnancy were assessed. A questionnaire was developed to obtained demographic, socio-economic, anthropometric, drug and medical history. Using 24-hour food recall for three days in a row, their food intake was assessed and then converted to nutrients intake. The average BMI of the non-pregnant women was found 22.89 ± 3.4 kg/m^ and for pregnant women was found 23.52 ± 3.71 kgW. The mean dietary nutrients intake of dietary fiber, calorie, protein, fat, carbohydrate, calcium, iron, thiamine, riboflavin, vitamin C, Vitamin A, folate, vitamin Bg and Vitamin B12 of the pregnant mothers was 4.38 g, 1619 kcal, 60.05 g, 30.38 g, 268.79 g, 537.21 mg, 21.53 mg, 1.15 mg, 0.94 mg, 97.36 mg, 647.6 jUg, 153.93 jUg, 1.41 mg and 4.09 fig respectively. Most of pregnant women (more than 90%) failed to meet their energy, calcium and folate requirement. Most of the pregnant mother in Bangladesh can not fulfill their dietary requirements during pregnancy. Bangladesh J. Nutr. Vol. 26-27, December 2014, P: 75-85